Aelia Capitolina - Jerusalem in the Roman period: in light of archaeological research - Ṿeḳsler-Bdolaḥ, Shlomit (Mnemosyne, 2020)
"The book discusses the history and the archaeology of Jerusalem in the Roman period (70-400 CE) following a chronological order, from the establishment of the Tenth Roman Legion's camp on the ruins of Jerusalem at 70 CE, through the foundation of Aelia Capitolina by Hadrian, in around 130 CE, and the Christianization of the population and the cityscape in the fourth century. Cemeteries around the city, the rural hinterland, and the imperial roads that led to and from Aelia Capitolina are discussed as well. Due to the paucity of historical sources, the book is based on archaeological remains, suggesting a reconstruction of the city's development and a discussion of the population's identity"--